Genre Takhrīj Karya Fiqh Shāfī‘Iyyah: Studi Komparasi antara Al-Tadhhīb dan Irshād Al-Faqīh - Ahwan Fanani (Universitas Islam Negeri Mataram, 2014)
The availability of works representing madhhab’s legal opinions attracted law scholars of each school of law to extract the most authoritative of the works in ikhtiṣār (extract works). However, then, the existence of ikhtiṣār also creates a need to wider explanation of the selected opinion in the form of sharḥ (commentary works). There are several models of sharḥ, one of which is commentary using takhrīj approach which then creates a distinguished genre. This article is aimed at comparing two ikhtiṣār works using the approach, Irshād al-Faqīh ila Ma‘rifah Adillah al-Tanbīh and al-Tadhhīb fi Adillah Matn al-Gāyah wa al-Taqrīb. It is found that both works have different aim and structure. Irshād al-Faqīh is more traditionist version of sharh, while al-Tadhhīb is more law specialist one.